Pulmonary function analysis in carpenters: a study from Kerala - Pandarikkal, Jagadees R.; Kurien, Annamma; Paul, Davis (International Journal of Research in Medical Sciences, 2018)
Background: There has been an increase in proportion of workers suffering from occupational diseases compared to past. Only limited studies have been conducted to evaluate the pulmonary functions of carpenters, exposed to wood dust. Hence the present study was undertaken to find out any functional impairment in carpenters due to their occupational environment. Methods: Study was done in 300 subjects who were divided into two groups of 150 each. One group comprised carpenters with minimum 5 years exposure to wood dust. Other group comprised matching healthy subjects who served as controls. Pulmonary function parameters were recorded from all subjects. Parameters recorded were SlowVital Capacity (SVC), Forced Vital Capacity (FVC), Forced Expiratory Volume in 1 second (FEV1), and Peak Expiratory flow Rate (PEFR). ‘Knudson and Collagens’ standard reference values for south Indians were used here for interpretation. Statistical analysis of the data of study subjects and the controls were done by using student’s ‘t’ test. The level of significance was fixed as 5%. Results: A statistically significant reduction in SVC, FVC, FEV1and PEFR was seen in the study group compared to control group. FEV1/FVC was less than 80% of the predicted values in 8% of the study population. Seventeen percentage of the study population had less than 80% of predicted value of both FEV1 and FVC with normal FEV1/FVC. Conclusions: Lung functions of carpenters show statistically significant reduction compared to normal healthy adults. This could be due to their exposure to wood dust.